2021
DOI: 10.1002/zamm.202100128
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady flow of Williamson fluid under the impact of prescribed surface temperature (PST) and prescribed heat flux (PHF) heating conditions over a stretching surface in a porous enclosure

Abstract: An unsteady mixed convection flow of Williamson nanofluid over a stretchable surface embedded in a porous medium is scrutinized numerically. Here the porous medium is characterized by Darcy Forchheimer model under the influence of a magnetic field. Heat transfer analysis with two different conditions namely, prescribed surface temperature (PST) and prescribed heat flux (PHF) are taken into account. The evolved mathematical model is numerically solved by utilizing the Keller box method and bvp4c solver in MATLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In order to increment in Fr, the temperature distribution θ (η) of all Ag-Blood, TiO 2 -Blood and Fe-Blood is significantly accelerated. This result is consent to the work done by (26) .…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In order to increment in Fr, the temperature distribution θ (η) of all Ag-Blood, TiO 2 -Blood and Fe-Blood is significantly accelerated. This result is consent to the work done by (26) .…”
Section: Resultsmentioning
confidence: 72%
“…Physically, when the value of ϕ rises, the temperature profile rises, which is caused by the collision of the suspended nanoparticles. Physically, when nanoparticles are added, thermal conductivity rises, and the thickness of the temperature field rises as well (26) . Figure 9 depicts the deviation in velocity distribution f ′ (η) for differing Forchhiemer number Fr.…”
Section: Resultsmentioning
confidence: 99%
“…They observed that the increasing contributions of magnetic field and porosity factors are thought to be slowing the flow rate. Chandel and Sood [11] inspected the buoyancy magneto flow of Williamson fluid induced by nanofluid across a stretchy sheet in a porous media. It is stated that buoyancy ratio and mixed convective parameters increase fluid velocity.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of publications may be quoted that highlight the importance of both types of boundary conditions. Chandel and Sood 34 investigated the effects of the PST and the PHF heating constraints on the unsteady flow of a Williamson nanofluid across an extendable surface embedded in a spongey medium. It is found that under both temperature conditions (PST/PHF), the heat transfer rate increases which may be useful in cooling procedures.…”
Section: Introductionmentioning
confidence: 99%